Analysis of flow behaviour of an aluminium containing austenitic steel - Satyanarayana D.V.V.; Malakondaiah G.; Sarma D.S. (My University, 2025)
Experimental true stress-true strain data, at both ambient and elevated temperatures, of an Fe-Ni-Cr-Al alloy in solution treated as well as aged conditions have been analysed using different flow relationships. Ludwigson relationship provides the best fit of the data for all the conditions investigated, though all the relationships, except Voce, describe the flow behaviour well at a high temperature of 673 K. The transition in macroscopic flow behaviour of the alloy with strain, in solution treated condition, can be correlated with the transition in dislocation mechanism from planar slip in low strain regime to slip plus deformation twinning in the high strain regime. Although ageing does not appear to alter the macroscopic flow behaviour, it causes considerable change in flow parameters of the Ludwigson relationship and substructural evolution. The flow data of the aged alloys fitted according to Ludwigson model not only yield a unique set of flow parameters for each ageing condition but also exhibit a systematic trend with ageing time. The transition in macroscopic flow behaviour of the alloy with strain, in aged conditions, can be correlated with a change in dislocation mechanism from dislocation-precipitate interaction at lower strains to dislocation-dislocation interaction at higher strains leading to formation of a dense dislocation tangled networks in the matrix regions surrounding the precipitates. © 2006.